Eduardo Palacios, Eduardo Tzili-Apango y Jaqueline Briceño, Los olvidados de Eurasia. Aportaciones desde México - Raya López, Oscar Abraham (El Colegio de México A.C., 2023)
Los olvidados de Eurasia. Aportaciones desde México, coordinated by Eduardo Palacios, Eduardo Tzili-Apango, and Jaqueline Briceño (2023), is a book focused on the study of countries, including their international relations, which are not very well known in the Mexican academia. Those are Moldova, Belarus, Armenia, Azerbaijan, Georgia, Tajikistan, Kyrgyzstan, Turkmenistan, Mongolia, Nepal, Laos, Myanmar and East Timor. It is true that, at first glance, all these countries may not attract a lot of attention because they supposedly lack fame and importance in the world and respective regions where they belong, however, this is a misconception. Both the coordinators and guest authors, Mexican and foreign, build a solid argument to prove the importance of those States. In an international system that is looking to be more multipolar and complex, looking at nations such as these is an obligatory task for Mexico, Latin America, and the rest of the world.